Effects of Cryptocurrencies on Global Economics: A Review Study - Rogash Younis Masiha (Qubahan Academic Journal)
The features of a new global economy appear stronger and faster than the changes recorded by the economy throughout history, and the “Covid-19” pandemic has accelerated these transformations, achieving on the ground a global experience to deal with digital payment via credit cards and the use of online payment applications, and it marks the beginning of the end of the era of paper currencies. And the trend towards investing in crypto and digital currencies on the part of investors, in conjunction with the competition of countries around the world to win the issuance of the first digital currency issued by central banks. There are many questions about replacing the digital currency with gold or the dollar in a rapid transformation that changes the trends of the global economy, and the number of cryptocurrencies around the world has reached about 4337 currencies with a market value of $ 1.003 trillion, “Bitcoin” holds the largest share by 66% with a market value of $ 664 billion. Despite many official warnings against investing in these unregulated currencies, fintech startups are witnessing a surge in demand from consumers who are rushing to invest in cryptocurrencies amid great interest and momentum in Bitcoin. Like Revolut, eToro and Luno, cryptocurrency demand surged on their platforms amid the resurgence of Bitcoin prices.